2021
DOI: 10.1016/j.ejon.2021.101958
|View full text |Cite
|
Sign up to set email alerts
|

The cost of living with cancer during the second wave of COVID-19: A mixed methods study of Danish cancer patients' perspectives

Abstract: This study investigated experiences and levels of distress and resilience of Danish cancer patients during the second wave of the COVID-19 pandemic. Methods: The mixed methods design included a subset of cancer patients who responded to a cross-sectional survey in May 2020. Data were collected through telephone interviews. The National Comprehensive Cancer Network Distress Thermometer (NCCN DT), and Connor-Davidson-Resilience Scale (CD-RISC2) were used to measure distress and resilience. Data were analysed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 31 publications
8
24
0
1
Order By: Relevance
“…Increased prevalences of psychological disorders during the COVID-19 pandemic and decline in psychological wellbeing have been described similarly to our results [ 28 , 29 ]. Other studies reported higher rates [ 30 , 31 , 32 , 33 ], but used instruments targeting different aspects of distress.…”
Section: Discussionsupporting
confidence: 91%
“…Increased prevalences of psychological disorders during the COVID-19 pandemic and decline in psychological wellbeing have been described similarly to our results [ 28 , 29 ]. Other studies reported higher rates [ 30 , 31 , 32 , 33 ], but used instruments targeting different aspects of distress.…”
Section: Discussionsupporting
confidence: 91%
“…Hamlish and Papautsky (2020) [53] reported higher levels of distress in White breast cancer patients compared to Non-white participants. In contrast, other research teams found that levels of distress among cancer patients were lower or no different than before the pandemic [ 19 ; 31 ; [54] , [55] , [56] ]. Even more, one study found no difference in anxiety or depression levels in cancer patients compared to the general population during the COVID-19 pandemic [57] .…”
Section: Resultsmentioning
confidence: 84%
“…Studies used many different outcome measures in their cross-sectional designs ( Table 1 ). Six studies employed a qualitative methodology [23] , [24] , [25] , [26] , [27] , [28] and four study used mixed methods [29] , [30] , [31] , [32] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations